2020
DOI: 10.1038/s41598-019-57020-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential Distribution of Asian Gypsy Moth in Canada: A Comparison of Two Methodological Approaches

Abstract: Gypsy moth (Lymantria dispar L.) is one of the world's worst hardwood defoliating invasive alien species. it is currently spreading across north America, damaging forest ecosystems and posing a significant economic threat. Two subspecies L. d. asiatica and L. d. japonica, collectively referred to as Asian gypsy moth (AGM) are of special concern as they have traits that make them better invaders than their European counterpart (e.g. flight capability of females). We assessed the potential distribution of AGM in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…The AUC value of habitat suitability model for Malayan gaur was 0.84, indicating good performance of accuracy. AUC values greater than 0.9 usually indicate high accuracy, values between 0.7 and 0.9 indicate good accuracy and values between 0.5 and 0.7 indicate low accuracy (Srivastava et al, 2020). Distance from urban areas indicated the highest relative contribution to the model (26.9%) suggesting it to have the most useful information, followed by distance from water body (24.2%) and land use (18.0%).…”
Section: Resultsmentioning
confidence: 99%
“…The AUC value of habitat suitability model for Malayan gaur was 0.84, indicating good performance of accuracy. AUC values greater than 0.9 usually indicate high accuracy, values between 0.7 and 0.9 indicate good accuracy and values between 0.5 and 0.7 indicate low accuracy (Srivastava et al, 2020). Distance from urban areas indicated the highest relative contribution to the model (26.9%) suggesting it to have the most useful information, followed by distance from water body (24.2%) and land use (18.0%).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, background sample considered in the model may include both “true” and “false” absences (Gallien et al., 2012). To analyze the adequacy of the models, we checked the ClimEurope model adequacy when projected in Asia and ClimAsia when projected in Europe (Srivastava et al., 2020). Finally, another SDM model called ClimEuropeWeighted was calibrated with occurrence data from Europe (the same that were used in ClimEurope) but background data were weighted with the ClimAsia projection in Europe.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate and project the distribution of the Caucasian grouse, we used maximum entropy modeling (Maxent; Phillips, Dudík, & Schapire, 2004). Maxent, the most widely used SDM algorithm (Phillips et al, 2004), is a presence-only modeling technique (Elith et al, 2011), and has been consistently shown to outperform alternative approaches (Elith et al, 2006;Merow, Smith, & Silander, 2013;Srivastava, Griess, & Keena, 2020), especially when the number of presence records is small (Filz & Schmitt, 2015). To identify the best Maxent parameterization, we used the "kuenm" package in R (Cobos, Peterson, Barve, & Osorio-Olvera, 2019).…”
Section: Species Distribution Modelingmentioning
confidence: 99%